Morphologie und Moderne : Goethes : nschauliches Denken9 in den Geistes- und Kulturwissenschaften seit 1800. - Maatsch, Jonas (Klassik und Moderne., 2014)
Although Goethe's Morphology drew little notice from natural scientists, his way of conceptualizing the innumerable forms that occur in nature as organic variations of a few basic archetypes was received with immediate interest by scholars in the humanities. This volume compiles studies on Droysen, Dilthey, Simmel, and Wittgenstein, who relied on Goethe's Morphology trying to master a modern age experienced as increasingly confusing.